Multiplex PCR-based assay for detection of Bordetella pertussis in nasopharyngeal swab specimens. - Wadowsky, R M (1996)
A multiplex PCR-based assay was developed for the detection of Bordetella pertussis in nasopharyngeal swab specimens. The assay simultaneously amplified two separate DNA targets (153 and 203 bp) within a B. pertussis repetitive element and a 438-bp target within the beta-actin gene of human DNA (PCR amplification control). PCR products were detected by a sensitive and specific liquid hybridization gel retardation assay. A total of 496 paired nasopharyngeal swab specimens were tested by both the PCR-based assay and culture. Although 30 (6%) of the specimens inhibited the amplification of the beta-actin target, in all 29 specimens studied, the inhibition disappeared on repeat testing or was easily overcome with a 1:8 dilution or less of specimen digest. Of the 495 specimen pairs yielding a final evaluable result by the PCR-based assay, 19.0% were positive by the PCR-based assay, whereas 13.9% were positive by culture (P < 0.0001). After resolving the PCR-positive, culture-negative results by testing an additional aliquot from these specimens by the multiplex PCR-based assay, the PCR-based assay had a sensitivity and specificity of 98.9 and 99.7%, respectively, compared with values of 73.4 and 100%, respectively, for culture. In comparison with patients with culture-confirmed pertussis, those with PCR-positive, culture-negative results were older and more likely to have had prolonged cough, immunization with pertussis vaccine, or treatment with erythromycin. This multiplex PCR-based assay is substantially more sensitive than culture and identifies specimens that contain inhibitors of PCR.